Eating disorders and their relationship with menopausal phases among a sample of middle-aged Lebanese women - Joe Khalil; Sarah Boutros; Nelly Kheir; Maha Kassem; Pascale Salameh; Hala Sacre; Marwan Akel; Sahar Obeid; Souheil Hallit (BMC Women's Health, 2022)
Abstract Objectives The objective of our study was to evaluate the association between the transition to menopause, body dissatisfaction, and abnormal eating habits (restrained eating, binge eating, and orthorexia nervosa) in a sample of middle-aged Lebanese women. Methods A cross-sectional study conducted between July 2019 and January 2020 enrolled 1001 women aged 40 years and above from all Lebanese governorates. Data were collected by face-to-face interviews with all participants. The Body dissatisfaction subscale of the Eating Disorder Inventory‑second version was used to assess body dissatisfaction, whereas the Binge Eating Scale, Dutch Restrained Eating Scale, ORTO-15, Dusseldorf Orthorexia Scale (DOS), and Teruel Orthorexia Scale (TOS) were used to assess eating disorders (binge eating, restrained eating and orthorexia nervosa respectively. Multivariable analysis of covariance (MANCOVA) was used to compare multiple measures among the three menopausal phases, after adjustment over potential confounding variables (age, monthly income, body mass index, marital status, education level, and body dissatisfaction). Results Postmenopause was significantly associated with more orthorexia nervosa tendencies (lower ORTO-15 scores) than premenopause (β = − 1.87; p = 0.022). Perimenopause was associated with more binge eating (β = 1.56; p = 0.031), and less orthorexia nervosa (as measured by the DOS) than premenopause, with this association tending to significance (β  = − 1.10; p = 0.051). Furthermore, higher body dissatisfaction was significantly associated with higher restrained eating (β = 0.02; p < 0.001), binge eating (β = 0.48; p < 0.001), and orthorexia nervosa as measured by ORTO-15 (β = − 0.17; p < 0.001) and TOS (β = 0.08; p = 0.002), but not DOS. Conclusion Our study showed that menopausal stages are associated with some disordered eating behaviors (binge eating and orthorexia nervosa) among middle-aged women. Those results may serve as a first step towards spreading awareness among women within this age group regarding eating attitudes. Moreover, healthcare professionals should screen for the presence of disordered eating during those women’s routine visits to the clinics.